Memanfaatkan Peluang dari Fasilitasi Perdagangan ASEAN Melalui ASEAN Single Window System Menuju ASEAN Economic Community (AEC) 2016 - Primadiana Yunita (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2016)
The ASEAN Economic Community (AEC) which begins in 2016 will be new chapter for economic of ASEAN .One of the framework was proclaimed in speed up the implementation of AEC is to reduce trade barriers through ASEAN trade facilitation. ASEAN Trade Facilitation intended to provide many facilities trade in the asean region, expected to increase the volume of trade between asean countries . One of ASEAN's efforts in trade facilitation is the establishment of the National Single Window each member that will be integrated into the ASEAN Single Window (ASW). This paper wants to analyze the dilemma of implementation of the ASEAN Single Window and the opportunities that may be utilized by ASEAN member countries of the ASW's.